PROSES PEMBERDAYAAN PADA KELUARGA PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN DALAM PERTEMUAN PENINGKATAN KAPASITAS KELUARGA SESI PENGELOLAAN KEUANGAN (STUDI DESKRIPTIF DI KELURAHAN SRENGSENG SAWAH, KECAMATAN JAGAKARSA, KOTA JAKARTA SELATAN, PROVINSI DKI JAKARTA) - P., R. Arlingga Hadistira A.; Machdum, Sari Viciawati (UI Scholars Hub, 2021)
This research is descriptive qualitative research that discusses the financial management of beneficiary (KPM) of Program Keluarga Harapan (PKH) organized by the Ministry of Social Affairs of the Republic of Indonesia in Srengseng Sawah Village, Janggakarsa District, South Jakarta. Data collection in this study was conducted through observation and interviews with purposive sampling technique. This study generally aims to see the process of empowering beneficiaries of the Program Keluarga Harapan in the Family Capacity Building Meeting (P2K2) or Family Development Session (FDS) in Srengseng Sawah Village and to determine the role of assistants in implementing P2K2 Financial Management Sessions in Srengseng Sawah Village. The results of the study indicated that in implementing P2K2 Financial Management Sessions, there were several obstacles and problems. From the KPM PKH side, there are problems, such as: (1) not being able to differentiate between needs and wants and (2) unable to regulate expenses that must be prioritized, postponed, reduced, or eliminated. In terms of PKH human resources, there are obstacles in making KPM PKH stay focused during P2K2 because the composition of the Companion versus KPM is not ideal. Through this research also found a positive impact that occurred after the empowerment process in P2K2 Financial Management Sessions. Among them, the knowledge and expertise in making monthly budgets and saving plans have been implemented by most of the KPM PKH, resulting in reduced debt, the ability to better manage household finances which leads to better economic conditions.